Assessment of a quality improvement intervention to improve the consistency of total body surface area burn estimates between referring facilities and a pediatric burn center. Issue 8 (December 2019) - Manning Ryan, Leticia; Costabile, Philomena; Ziegfeld, Susan; Puett, Lisa; Turner, Amiee; Strockbine, Valerie; Klein, Bruce L.
Highlights: Referring facilities often overestimate the total body surface area of burns in comparison to the pediatric burn center. Such discrepancies may trigger inappropriately aggressive interventions with potential for patient harm. The consistency can be improved by sharing a common clinical assessment tool and standardization of the intake process. Abstract: Background: Burns are a significant source of pediatric morbidity and frequently result in transfer of care to a pediatric burn center. Data suggest that referring facilities often overestimate the total body surface area (%TBSA) of burns in comparison to the subsequent assessment at the pediatric burn center. Such discrepancies may trigger inappropriately aggressive interventions with potential for patient harm. Our baseline assessment of data from 106 patients transferred to our pediatric burn center over a one-year period showed that 59/106 (56%) patients had a %TBSA recorded at the time of transfer and 18/59 (31%) had clinically significant differences (>5% difference) in estimates between the referring facility and the pediatric burn center. Methods: Informed by this clinical audit and a root cause analysis, we implemented practices to enhance consistency of clinical assessments between referring facilities and our pediatric burn center. These practices included the use of a common clinical assessment instrument (a standardized Lund and Browder form) that was integrated into the interfacility transfer process as well as educational outreach at referring facilities for providers who treat children with burns, prioritizing facilities with the highest number of discrepancies. Results: Follow up data was reviewed 16–23 months after initiating the intervention. Cumulatively, we found significant improvement in the proportion of patients with %TBSA recorded (94% vs 56%, p < 0.001) that achieved our goal to exceed 90% and a reduction in clinically significant discrepancies that exceeded our goal of 15% (10% vs 31%, p = 0.002). Conclusions: Referring facilities often overestimate the %TBSA in comparison to the subsequent assessment at the pediatric burn center. The consistency of the %TBSA estimates can be improved by interventions that utilize the sharing of a common clinical assessment instrument and standardization of the transfer intake process.